Determinants of inward FDI in Ukraine: Does political stability matter? - Andrzej Cieślik; Oleg Gurshev (International Journal of Management and Economics, 2020)
The main goal of this article is to study the determinants of foreign direct investment (FDI) in Ukraine from 2013 to 2017 that includes the years of armed conflict. We adopt the Knowledge-Capital model as our analytical framework and extend it to include the effects that account for political stability and political regime. The research hypotheses obtained from this framework are verified using the Pseudo-Poisson Maximum Likelihood estimation technique and the bilateral panel data on direct investment stocks from 140 partner countries. Our empirical findings show that access to Ukraine's cheap labor force is the primary reason for inward FDI. Moreover, we find no direct relationship between the political events in Ukraine and the investment stock dynamics as the estimated parameters on the indices of democracy, autocracy, polity, and political stability show no statistical significance.
Keywords: F23; P33; 650; foreign direct investment; political stability; Pseudo-Poisson maximum likelihood; Ukraine